Analisa Komparasi Konsep Sumber Daya Insani (SDI) Konvensional dan Syari’ah - Nugrahaeni Fitroh R. Syakarna; Krismonika Krismonika; Nurul Azizah (Universitas Muhammadiyah Ponorogo, 2021)
One of the important resources in management is human resources. The importance of human resources can be felt in managing a company or organization. Regardless of the advancement of technology today, the human resource factor is still very much needed in playing a role for the success of an organization. The quality of human resources is an absolute requirement to start development. In the view of Islam everything must be done in an orderly and orderly manner and should not be carelessly. The role of human resources in this matter greatly determines the pace of a company/organization to run directed. Human resources are human potentials as a driving force for an organization to realize its existence. Islamic human resources require an education program that is entirely pure sharia and not contaminated with conventional elements. In essence, reliable human resources based on sharia must be placed on the foundation of spiritual awareness (servants of Allah) and rational (khalifah Allah). There is no contradiction between spiritual consciousness and rational consciousness in Islamic economics. As servants of Allah, humans become obedient creatures who always carry out Allah commands and stay away from His prohibitions, and as Allah's khalifah, humans become successful and successful creatures through the support of science.